Quintana Trias, Lluís. Arte y blasfemia. El caso Veronese. Barcelona: Fragmenta Editorial, 2019 [ISBN: 978-8417796150] - Arribas Ramos, Lara (Eikón / Imago, 2023)
Book review of Quintana Trias, Lluís. Arte y blasfemia. El caso Veronese. Barcelona: Fragmenta Editorial, 2019 [ISBN: 978-8417796150]